2017
DOI: 10.1155/2017/5240186
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Permeability Characteristics of Polyurethane Soil Stabilizer Reinforced Sand

Abstract: A polymer material of polyurethane soil stabilizer (PSS) is used to reinforce the sand. To understand the permeability characteristics of PSS reinforced sand, a series of reinforcement layer form test, single-hole permeability test, and porous permeability test of sand reinforced with PSS have been performed. Reinforcement mechanism is discussed with scanning electron microscope images. The results indicated that the permeability resistance of sand reinforced with polyurethane soil stabilizer is improved throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Yang et al [19] studied the effects of aging tests on a novel chemical sand-fixing agent (polyaspartic acid resin). These polymer materials can change the loose structure and improve the strength by filling up the void spaces and enwrapping the sand particles [20][21][22]. These research results indicated that the polymeric materials can be considered as a soil stabilizer to improve the strength characteristics of sand.…”
Section: Sandmentioning
confidence: 99%
“…Yang et al [19] studied the effects of aging tests on a novel chemical sand-fixing agent (polyaspartic acid resin). These polymer materials can change the loose structure and improve the strength by filling up the void spaces and enwrapping the sand particles [20][21][22]. These research results indicated that the polymeric materials can be considered as a soil stabilizer to improve the strength characteristics of sand.…”
Section: Sandmentioning
confidence: 99%
“…All the mentioned research achievements illustrate that these methods can usefully improve the sand behaviors. There are many studies on increasing strength, reducing permeability, improving the resistance to liquefaction, and weathering action [30,31,32,33,34]. However, very limited studies are carried out to evaluate the behaviors of composite materials after immersion.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, polymeric materials are introduced to enhance sand cohesion and can form a unitary coherent matrix with much smaller environmental impacts (e.g., water pollution and vegetation growth) than the above additives. Previous studies have shown the possibility of using polymers to strengthen soil, reduce permeability, and control soil erosion [10,11,12,13,14,15]. This is mostly benefited from the particle elements being closely joined and finely structured by these polymeric matters.…”
Section: Introductionmentioning
confidence: 99%